A reinforced PDMS mold for hot embossing of cyclic olefin polymer in the fabrication of microfluidic chips. Issue 23 (11th November 2022) - Qin, Yuling; Kreutz, Jason E.; Schneider, Thomas; Yen, Gloria S.; Shah, Eleanor S.; Wu, Li; Chiu, Daniel T.
Abstract : A reinforced PDMS mold for hot embossing of cyclic olefin polymer in the fabrication of microfluidic chips was developed, which facilitates the rapid validation of microfluidic designs. Abstract : Hot embossing is a cost-effective and flexible fabrication technology with high replication accuracy for feature sizes as small as 50 nm. Here we develop a reinforced polydimethylsiloxane (PDMS) mold for hot embossing of cyclic olefin polymer (COP) sheets in the fabrication of microfluidic chips and demonstrate the method by fabricating chips for automated sample digitization in digital nucleic acid assays. The PDMS is hardened by adding an investment powder as a dopant and is constrained with an aluminum frame to prevent lateral expansion during hot pressing. The reinforced PDMS mold demonstrated excellent performance in hot embossing (180 °C, 103 kPa, 5 min) for micropatterning COP sheets, with highly reproducible features as small as 10 μm (width of draining channel). In contrast, the microscale features were inconsistent and distorted when omitting either the investment powder or frame from the PDMS mold. COP chips were assembled by thermally bonding patterned and unpatterned COP sheets. We tested the performance of the COP chip for automated sample digitization in a digital LAMP assay used to quantify human papillomavirus-18 (HPV-18) DNA. A mixture of nucleic acid amplification reagents was loaded into the main channel of the chip using a syringe pump, then the solution was spontaneously partitioned into chambers (∼0.6 nL), which were then isolated by flowing oil through the chip. The digital LAMP assay produced accurately absolute quantitation of DNA at concentrations ranging from 10 to 1000 copies per μL. The strategy presented here provides a simple, low-cost method to prepare molds for hot embossing, which facilitates rapid validation of microfluidic designs.